Frequency and characteristics of anemia in hypothyroid patients: A cross-sectional study - Abdullah S. Babaker; Reem M. Al-Qahtani (Journal of Family and Community Medicine)
BACKGROUND: Hypothyroidism leads to a metabolic slowdown that affects all body systems and significantly impacts the hematopoietic system, resulting in anemia in 20%–60% of patients. This study aims to evaluate the prevalence of anemia in hypothyroid patients and describe the factors associated with anemia in those patients. MATERIALS AND METHODS: We reviewed the electronic health records (EHRs) of all the patients attending the Outpatient Department of King Abdulaziz University Hospital, Jeddah, Saudi Arabia, during January 1, 2018, to December 31, 2022. All patients aged 18-70 years who had received a diagnosis of hypothyroidism, ICD-10 code E03.9, and had undergone simultaneous blood tests for complete blood count and iron profile along with thyroid function tests were included in the study. Data on demographic characteristics, laboratory test results, and comorbidities was retrieved from EHRs. Anemia was defined according to WHO as Hb levels <12.0 g/dL in women and <13.0 g/dL in men. Data was analyzed using SPSS version 28.0. Categorical variables were presented as frequencies and percentages while continuous variables were described by mean and standard deviation. Multiple logistic regression was applied to determine the risk factors for hypothyroidism. RESULTS: Study included a total of 413 patients with hypothyroidism; 40% of hypothyroid patients were found to be anemic and most had microcytic normochromic anemia. Logistic regression revealed that males had much lower risk of anemia compared to females (adjusted odds ratio [AOR] = 0.14; 95% confidence interval [CI]: 0.05–0.39), while obesity was associated with a higher risk of anemia (AOR = 1.67; 95% CI: 1.11–2.50). CONCLUSION: A higher proportion of anemia was seen in patients with hypothyroidism, indicating a significant relationship between anemia, obesity, and gender. This highlights the importance of monitoring anemia in patients with hypothyroidism, especially in females and obese individuals.